Petrographic and Physiomechanical Investigation of Late Cretaceous Kawagarh Formation Kahi Section, Nizampur Basin - Ahmad, Mukhtar S.; Sajjad, Syed Muhammad Waseem; Khan, Emad Ullah; Sabir, Maria (International Journal of Economic and Environmental Geology, 2023)
The late Cretaceous Kawagarh Formation has been investigated in terms of field observation, and petrographic analysis, to understand the petrography and its impact on the geotechnical properties. The Kawagarh Formation is well exposed among the upper Indus Basin, and has been studied by various workers in different aspects. Kawagarh Formation exposed in Kahi section of Nizampur Basin has been selected in this study to know the behavior of carbonate rocks for engineering purposes. Lithologically, this formation is composed of thick to medium bedded, highly fractured limestone, marls, and dolomitic limestone which has undertaken diagenetic alteration including dolomite, calcite veins, and stylolites. Followed by petrographic analysis which reveals that the Kawagarh limestone is mostly fossiliferous comprised of a large number of planktonic foraminifera fossils like Globotruncana Hilli and Globotruncana Linneana fossils. Furthermore, to know the impact of petrographic minerals on engineering behavior, mechanical properties in terms of uniaxial compressive strength (UCS) and uniaxial tensile strength (UTS) were also computed by using a universal testing machine (UTM). The resultant mechanical values lie in the strong compressive strength and suggest their usage for various construction purposes. Aggregate degradation tests including water absorption, specific gravity, aggregate impact value, Los angles abrasion, and soundness was also computed according to the International standard organization, ASTM (American Society for testing materials) and British standard. The aggregate values of the Cretaceous Kawagarh Formation are within the defined standard limits and can be used as an aggregate source for different construction engineering projects.